Electrical Properties of poly Vinyl Alcohol (PVA) doped with Alizarin orang Azo dye thin films prepared by cast method. - D. Salem , Rusel (University of Thi-Qar Journal of Science, 2019)
The electrical properties investigation for poly Vinyl Alcohol (PVA) doped with Alizarin orang Azo dyfilms was carried out for films prepared by cast method. Conduction processes were analysed througmeasuring (Current – Voltage) and (Conductivity – temperature) relationships in the voltage and temperatureranges (1-250) V and (293 -333) K respectively. The resistance of the doped films is found to have negative thermal coefficient.The activation energy at temperature (293-333)K was about (0.74)eVis found from the ohmic region of the dark (current – voltage) characteristic. The conductivity at temperature293 K was equal to 1.2×10-10(S.cm-1).The deviation from ohm’s law has beeanalysed in term of the available conduction theories, Schotky conduction mechanism was concluded.